Human CRMP4 mutation and disrupted Crmp4 expression in mice are associated with ASD characteristics and sexual dimorphism. Issue 1 (December 2017) - Tsutiya, Atsuhiro; Nakano, Yui; Hansen-Kiss, Emily; Kelly, Benjamin; Nishihara, Masugi; Goshima, Yoshio; Corsmeier, Don; White, Peter; Herman, Gail; Ohtani-Kaneko, Ritsuko
Abstract Autism spectrum disorders (ASD) are more common among boys than girls. The mechanisms responsible for ASD symptoms and their sex differences remain mostly unclear. We previously identified collapsin response mediator protein 4 (CRMP4 ) as a protein exhibiting sex-different expression during sexual differentiation of the hypothalamic sexually dimorphic nucleus. This study investigated the relationship between the sex-different development of autistic features andCRMP4 deficiency. Whole-exome sequencing detected ade novo variant (S541Y) ofCRMP4 in a male ASD patient. The expression of mutated mouseCRMP4 S540Y, which is homologous to humanCRMP4 S541Y, in cultured hippocampal neurons derived fromCrmp4- knockout (KO) mice had increased dendritic branching, compared to those transfected with wild-type (WT)Crmp4, indicating that this mutation results in alteredCRMP4 function in neurons.Crmp4 -KO mice showed decreased social interaction and several alterations of sensory responses. Most of these changes were more severe in maleCrmp4 -KO mice than in females. The mRNA expression levels of some genes related to neurotransmission and cell adhesion were altered in the brain ofCrmp4 -KO mice, mostly in a gender-dependent manner. These results indicate a functional link between a case-specific, rare variant of one gene, Crmp4, and several characteristics of ASD, including sexual differences.